Baseline Hedgehog Pathway Activation and Increase of Plasma Wnt1 Protein Are Associated with Resistance to Immune Checkpoint Inhibitors in Advanced Non-Small-Cell Lung Cancer - Mehlman, Camille (Cancers (Basel), 2021)
SIMPLE SUMMARY: Wnt and Hedgehog (Hh) pathways are associated with stemness profile and with resistance to anti-tumor therapies. Pre-clinical data have suggested a role of these pathways in resistance to immune checkpoint inhibitors (ICIs). Here we evaluated the expression and levels of Shh and Wnt molecules both in plasma and tumor samples in a prospective cohort of 63 consecutive NSCLC patients treated with ICIs. We found that baseline Hh activation as assessed by nuclear staining of Gli1 was associated with poor outcome and high primary resistance rate. Increase of plasma Wnt1 during treatment was associated with resistance to ICIs. This is the first study to our knowledge to find an association between the Hh and Wnt pathways and resistance to ICIs in advanced NSCLC patients. We believe that these results are important to understand the molecular mechanisms associated with resistance to ICIs, and ultimately to improve future treatment strategies. ABSTRACT: Hedgehog (Hh) and Wingless-type (Wnt) pathways are associated with resistance to immune checkpoint inhibitors (ICIs) in preclinical studies. This study aimed to assess the association between expression and activation levels of Wnt and Sonic Hedgehog (Shh) pathways and resistance to ICIs in advanced NSCLC patients treated with ICI. Hh and Wnt pathways activation was assessed by immunohistochemistry (Gli1 and beta-catenin) on corresponding tumor tissues, and by plasma concentrations of Shh and Wnt (Wnt1, Wnt2 and Wnt3) at ICI introduction and at the first clinical evaluation. Sixty-three patients were included, with 36 patients (57.1%) with available tissue. Response rate was lower in Gli1+ NSCLC (20.0%) compared to Gli1 negative (Gli-) NSCLC (55.6%) (p = 0.015). Rate of primary resistance was 69.8%, vs. 31.2%, respectively (p = 0.04), and median progression-free survival (PFS) was 1.9 months (interquartile range (IQR) 1.2–5.7) vs. 6.1 months (1.6–26.0), respectively (p = 0.08). Median PFS and overall survival were shorter in case of increase of Wnt1 concentration during ICI treatment compared to other patients: 3.9 months vs. 11.2 months (p = 0.008), and 15.3 months vs. not reached (p = 0.003). In conclusion, baseline activation of Hh pathway and increase of Wnt1 concentrations during ICI treatment were associated with poor outcome in NSCLC patients treated with ICIs.